Life expectancy and healthy life years associated with diabetes in Germany. (30th September 2020) - Baumert, J; von der Lippe, E; Paprott, R; Du, Y; Reitzle, L; Heidemann, C; Schmidt, C; Scheidt-Nave, C
Abstract: Background: While life expectancy (LE) is rising, years lived with severe health impairments especially due to chronic diseases also increase. Diabetes is one of the major chronic diseases with high potential for co-morbidity and premature deaths needing life-long care. Therefore, information about loss in LE and healthy life years (HLY) in people with diabetes compared to people without diabetes is essential for assessing the burden of diabetes. Methods: Data on all-cause mortality rates for the general population of Germany in 2014 was drawn from the Federal Statistical Office; mortality rate ratios for people with diabetes compared to people without diabetes were based on claims data from about 70 million people covered by statutory health insurances in 2014. Data of three nationwide health telephone surveys conducted among adults in Germany 2009-2012 (n ∼ 60, 000) were used to assess severe health impairments defined as self-reported limitations in daily activities due to diseases for at least six months in people with and without diabetes. Based on these figures, estimates on LE and HLY could be calculated by sex and 5-year age-groups for people with and without diabetes aged ≥ 30 years. Results: In both sexes and in all 5-year age-groups, LE and HLY were substantially lower for people with than for people without diabetes. For example, among women in the age group 30-34 years, LE and HLY estimates were 48.0 and 36.4 years for those with diabetes compared to 54.9 and 47.6 years for those without diabetes; in men, these figures were estimated as 42.6 and 32.4 years for those with diabetes compared to 50.3 and 44.1 years for those without diabetes. Differences in LE and HLY between people with and without diabetes attenuated with increasing age. Conclusions: The present study revealed substantial reductions in LE and HLY related to diabetes and underlines the importance of integrating both figures in a national diabetes surveillance. Key messages: There are substantial differences in life expectancy and healthy life years between people with and without diabetes. Specific intervention and prevention activities should be implemented to tackle disability in persons with diabetes.